Differential expression of pectolytic enzyme genes in Xanthomonas citri subsp. citri and demonstration that pectate lyase Pel3 is required for the formation of citrus canker - Chang, Shih-Chieh; Deng, Wen-Ling; Huang, Hsiou-Chen; Chung, Kuang-Ren; Tzeng, Kuo-Ching (Microbiological research, 2016)
Bacterial canker, caused by Xanthomonas citri subsp. citri (Xcc), is one of the most destructive diseases of citrus. The pectolytic enzymes produced by phytobacteria are important virulence factors involved in tissue maceration, electrolyte loss and cell death of host plants. In this study, the promoter activity of the pectolytic enzyme genes pel1, pel2, pel3, pglA, and peh-1 were investigated in Xcc XW19 strain using the β-glucuronidase (GUS) gene as a reporter. GUS activity expressed under the control of the pel1, pel3, pglA, and peh-1 gene promoters positively correlated with bacterial growth. These gene promoters displayed high GUS activity in the presence of sodium polypectate. In addition, the four genes were induced in XVM2 minimal medium. However, only pel1 was subjected to catabolite repression by glucose. GUS activity was significantly enhanced in the XW19-derived reporter strains after they were inoculated into the leaves of Mexican lime and grapefruit, suggesting the involvement of the pel1, pel3, pglA, and peh-1 genes in XW19 pathogenesis. The pel3 promoter produced the highest GUS activity under all test conditions, whereas no GUS activity was detected using the pel2 promoter in vitro and in planta. In comparison with wild type Xcc, a pel3 mutant generated from Xcc XW19 using unmarked mutagenesis displayed reduced growth and induced smaller canker lesions on the leaves of Mexican lime, demonstrating that Pel3 of Xcc strain XW19 is a virulence factor.